TOBIN’S Q ANALYSIS AS AN INDICATOR USED IN MEASURING AND ANALYZING BANKING INDUSTRY OF COMPANIES LISTED IN KOMPAS100 PERIOD 2010-2014 - Hutabarat, Francis M.; Senjaya, Vianny Felicia (Prosiding Seminar Nasional INDOCOMPAC)
In globalization era, business world continues to develop in accordance to the demands of changing times. Capacity of the company to compete in the market will determine the performance of the company itself.  The value of the company reflects abstraction and performance of the company. If the company is certainly well worth, it is going to influence investors to invest in the company. The objective of this research is to analyzed the data given from companies listed in the Bank Sector at Kompas 100 using method of Tobin’s Q. This study aims to determine whether the value assigned by the market based on the number of sales of shares in the year multiplied by the share price at the end of last year that sought to be greater than the total of all assets of the company during the year. Results and conclusions showed  there are three companies in the undervalued categories namely BBNI, BBRI, BDMN, PNBN, BMRI, BJTM, BJBR, BBCA, BBKP in year 2010-2014, a company namely BBTN company touched the position of overvalued company at the year of 2011. Keywords: Tobin’s Q Method, Bankruptcy, Indonesian Stock Exchange